KONSEPTUALISASI PENDIDIKAN DALAM PANDANGAN ALIRAN FILSAFAT EKSISTENSIALISME - admin admin; Mohammad Ahyan Yusuf Sya’bani (TAMADDUN : Jurnal Pendidikan dan Pemikiran Keagamaan, 2017)
The background of this research is the philosophy of existentialism is one of the newcomers in philosophy world. The philosophy of existentialism is almost entirely a product of the twentieth century. Existentialism is essentially a school of philosophy that aims to restore the existence of human beings in accordance with the basic living conditions that are owned and faced. Therefore education is a human activity that continues to be implemented throughout the time it takes the study of the concept of education according to the philosophy of existentialism. Then this research produces the concept of education perspective philosophy of existentialism that is 1) the purpose of education, encouraging each individual to be able to develop all its potential for self-fulfillment; 2) education and schooling, education serves as an effort to preserve, conserve and pass on cultural heritage and schools in charge of educating children to make choices and decisions themselves by rejecting the authority of others; 3) the role of educators / teachers, teachers play a role in protecting and maintaining academic freedom; 4) the task of students, students are free to choose what they learn and how to learn it and students should be free to think and make their own decisions responsibly; 5) curriculum, emphasizing the individual as a source of knowledge about life and meaning; 6) learning materials, including theories, concepts, generalizations, principles, procedures, facts, terms, examples / illustrations, definitions, and prepositions.